2003
DOI: 10.1063/1.1538315
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-plane exchange coupling between epitaxial Ni (50 Å) and NiO (600 Å) bilayers

Abstract: We have investigated the exchange coupling between an epitaxial Ni ͑50 Å͒ film with an out-of-plane magnetic easy axis and a NiO ͑600 Å͒ film by polar magneto-optic Kerr-effect measurements. The temperature dependences of exchange field H E for both as-deposited and field-cooled states exhibit the same blocking temperature T B ϳ130°C. The exchange field H E for the field-cooled state is lower than that for the as-deposited state. The hard-axis in-plane loop shows a much smaller value of H E . No coercivity enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…in blue. We use the difference in Kerr signal intensity between up and down magnetic saturation for a given hysteresis loop (ΔI) normalized to the maximum intensity corresponding to a particular saturation state (I max ) as a measure of the quantity of ferromagnetic material 35 . Because MOKE does not measure the absolute magnetization, we cannot compare this quantity across samples.…”
Section: Resultsmentioning
confidence: 99%
“…in blue. We use the difference in Kerr signal intensity between up and down magnetic saturation for a given hysteresis loop (ΔI) normalized to the maximum intensity corresponding to a particular saturation state (I max ) as a measure of the quantity of ferromagnetic material 35 . Because MOKE does not measure the absolute magnetization, we cannot compare this quantity across samples.…”
Section: Resultsmentioning
confidence: 99%
“…It has been quite clear now that the exchange bias is strongly dependent on the spin configuration at the FM-AF interface, even though a theoretical model generally applies to a specific FM/AF system and is not valid for the other systems. In addition to the in-plane exchange bias which has been observed in the FM/AF systems with the in-plane anisotropy and has been investigated extensively, out-of-plane exchange bias has also been observed recently in FM/AF systems with the perpendicular anisotropy [6][7][8][9].…”
Section: Introductionmentioning
confidence: 93%
“…the FM easy axis lies in-plane. Recently, perpendicular exchange bias has been observed in exchange-biased FM layers or multilayers with out-of-plane easy axis after fieldcooling along the sample normal [7][8][9]. For both in-plane and out-of-plane (perpendicular) exchange bias, previous studies have shown that the bias can be related to the interfacial spin configuration and domain structures in the AFM layer [7,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 96%